Atmospheric forcing of the eastern tropical Pacific: A review - Magaña Rueda, Víctor Orlando (2006)
The increase in marine, land surface, atmospheric and satellite data during recent decades has led to an improved understanding of the air–sea interaction processes in the eastern tropical Pacific. This is also thanks to extensive diagnoses from conceptual and coupled ocean–atmosphere numerical models. In this paper, mean fields of atmospheric variables, such as incoming solar radiation, sea level pressure, winds, wind stress curl, precipitation, evaporation, and surface energy fluxes, are derived from global atmospheric data sets in order to examine the dominant features of the low level atmospheric circulations of the region. The seasonal march of the atmospheric circulations is presented to depict the role of radiative forcing on atmospheric perturbations, especially those dominating the atmosphere at low levels. In the tropics, the trade winds constitute an important north–south energy and moisture exchange mechanism (as part of the low level branch of the Hadley circulation), that determines to a large extent the precipitation distribution in the region, i.e., that associated with the Inter-Tropical Convergence Zone (ITCZ). Monsoonal circulations also play an important role in determining the warm season precipitation distribution over the eastern tropical Pacific through a large variety of air–sea–land interaction mechanisms. Westward traveling waves, tropical cyclones, low latitude cold air intrusions, and other synoptic and mesoscale perturbations associated with the ITCZ are also important elements that modulate the annual rainfall cycle. The low-level jets of the Gulf of California, the Intra-Americas Sea (Gulf of Mexico and Caribbean Sea) and Chocó, Colombia are prominent features of the eastern tropical Pacific low-level circulations related to sub-regional and regional scale precipitation patterns. Observations show that the Intra-Americas Low-Level Jet intensity varies with El Niño/Southern Oscillation (ENSO) phases, however its origin and role in the westward propagation and development of disturbances that may hit the eastern tropical Pacific, such as easterly waves and tropical cyclones, are still unclear. Changes in the intensity of the trade winds in the Caribbean Sea and the Gulf of Mexico (associated with eastern tropical Pacific wind jets) exert an important control on precipitation by means of wind–topography interactions. Gaps in the mountains of southern Mexico and Central America allow strong wind jets to pass over the continent imprinting a unique signal in sea surface temperatures and ocean dynamics of the eastern tropical Pacific. The warm pools of the Americas constitute an important source of moisture for the North American Monsoon System. The northeastern tropical Pacific is a region of intense cyclogenetic activity, just west of the coast of Mesoamerica. Over the oceanic regions, large-scale properties of key variables such as precipitation, moisture, surface energy fluxes and wind stress curl are still uncertain, which inhibits a more comprehensive view of the region and stresses the importance of regional field experiments. Progress has been substantial in the understanding of the ocean and atmospheric dynamics of the eastern tropical Pacific, however, recent observational evidence such as that of a shallow meridional circulation cell in that region, in contrast to the classic concept of the Hadley-type deep meridional circulation, suggests that more in situ observations to validate theories are still necessary.